The outcome of local excision of large rectal polyps by transanal endoscopic microsurgery - Tali Shaltiel; Rachel Gingold-Belfer; Boris Kirshtein; Nidal Issa (Journal of Minimal Access Surgery, 2023)
Introduction: Local excision of large rectal polyps can be an alternative for radical rectal resection with total mesorectal excision. We aim to report the functional and oncological outcomes of transanal endoscopic microsurgery (TEM) for patients with large rectal polyps. Methods: All demographic and clinical data of patients who underwent TEM for rectal polyp of 5 cm or more at the Hasharon Hospital from 2005 to 2018 were retrospectively reviewed. Results: Twenty-eight patients were included. The mean age was 66 years. The mean polyp size was 6.2 cm (range: 5–8.5 cm) with a mean distance of 8.3 cm from the anal verge. Peritoneal entry during TEM was observed in five patients and additional laparoscopy after the completion of the TEM was performed in four patients. There were no major perioperative complications. Seven patients had minor complications. Final pathology revealed T1 carcinoma in five patients and T2 carcinoma in three patients. Re-TEM was performed in one patient with involved margins with adenoma. After a median follow-up of 64 months, one patient had local recurrence. Conclusion: TEM is an acceptable technique for the treatment of large polyps with minor complications and a reasonable recurrence rate. TEM may be considered regardless of the size of the rectal polyp.